2018
DOI: 10.1371/journal.pone.0205825
|View full text |Cite
|
Sign up to set email alerts
|

The unequal vulnerability of communities of color to wildfire

Abstract: Globally, environmental disasters impact billions of people and cost trillions of dollars in damage, and their impacts are often felt most acutely by minority and poor communities. Wildfires in the U.S. have similarly outsized impacts on vulnerable communities, though the ethnic and geographic distribution of those communities may be different than for other hazards. Here, we develop a social-ecological approach for characterizing fire vulnerability and apply it to >70,000 census tracts across the United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
166
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(180 citation statements)
references
References 36 publications
(53 reference statements)
8
166
0
6
Order By: Relevance
“…We used the US Census Bureau for the American Community Survey (ACS) five-year estimates for the period 2011-2015 to select 21 social attributes (Table 1) to capture the level of resilience to wildfires at the scale of US block groups and communities (Cutter et al, 2003;Davies et al, 2018;Flanagan, Gregory, Hallisey, Heitgerd, & Lewis, 2011;Fothergill, 1996;Peacock, Morrow, & Gladwin, 1997;Wigtil et al, 2016;Wright, Rossi, Pereira, & Weber-Burdin, 2012). Social conditions, including wealth, poverty, race and age can often influence wildfire preparation and mitigation (Nielsen-Pincus, Ribe, & Johnson, 2015;Paveglio, Brenkert-Smith, Hall, & Smith, 2015;Paveglio et al, 2018;Wigtil et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…We used the US Census Bureau for the American Community Survey (ACS) five-year estimates for the period 2011-2015 to select 21 social attributes (Table 1) to capture the level of resilience to wildfires at the scale of US block groups and communities (Cutter et al, 2003;Davies et al, 2018;Flanagan, Gregory, Hallisey, Heitgerd, & Lewis, 2011;Fothergill, 1996;Peacock, Morrow, & Gladwin, 1997;Wigtil et al, 2016;Wright, Rossi, Pereira, & Weber-Burdin, 2012). Social conditions, including wealth, poverty, race and age can often influence wildfire preparation and mitigation (Nielsen-Pincus, Ribe, & Johnson, 2015;Paveglio, Brenkert-Smith, Hall, & Smith, 2015;Paveglio et al, 2018;Wigtil et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the 173 dead during the 2009 Black Saturday fires in Australia, 118 perished while sheltering in structures (Blanchi, Whittaker, Haynes, Leonard, & Opie, 2018), with 13% of all victims aged less than 18 (a substantial majority were under 15) and 16% aged 70 or over (Teague, McLeod, & Pascoe, 2010). These incidents revealed that differences in social vulnerability, defined as the adaptive capacity to absorb, recover and modify exposure to wildfires (Davies, Haugo, Robertson, & Levin, 2018), can affect the magnitude and duration of impacts like the loss of property, livelihoods, or services. Those hazards become disasters specifically when they affect socially vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have found that responses after disturbances often are most damaging for poor and marginalized groups (e.g. Davies, Haugo, Robertson, & Levin, 2018) and exacerbate existing inequalities—resources are often directed to people and places that have power and capacity to make their political voices heard (Mockrin et al, 2016; Nohrstedt & Weible, 2010; Tompkins & Adger, 2004). Emergency management is often disconnected from integrated planning processes that might identify needs and opportunities for improving community response, with the result that emergencies are not capitalized upon as opportunities for change.…”
Section: Looking Beyond Resiliencementioning
confidence: 99%